COMPARATIVE ANALYSIS OF THE GREAT GATSBY" BY F. SCOTT FITZGERALD AND "O’G’RI" BY HAMID OLIMJON. - Umaraliyeva Munojatxon Mashrabovna; Voxobjonova Shukurona Shuxratjon qizi (Лучшие интеллектуальные исследования, 2023)
This article primarily focuses on the comparative analysis of two different works, which are The great Gatsby written by F.Scott Fitzgerald and O'g'ri written by Hamid Olimjon.There are some similarities and differences between these two writers's work which must be addressed accordingly.